Collapse of Better Place: A Managerial Cognition Perspective on the Failure of an Entrepreneurial Initiative - Lin, Mei-Hsing; Chou, Hsin-Hui (Frontiers in Psychology, 2022)
For any entrepreneurial initiative, its survival depends on a working business model that could create value for the customers, and simultaneously, allow the firm to capture value from what has been created. Despite the increased attention on business model research, the understanding of its influence on the entrepreneurial development is quite constrained. In particular, the question of how an entrepreneurial firm’s business model is affected by its organizational member’s socio-cognition remains under-explored. To tackle this research question, we drew a linkage between business model literature and socio-cognitive approach to build the theoretical foundation. We used this theoretical lens to investigate the failure of Better Place, an Israel entrepreneurial company focusing on its proprietary battery-swap electric vehicles. In findings we argue that organizational members’ cognition shaped shared mental models of entrepreneurial firms, which are affected by both supply-push and demand-pull power, and are critical to firms’ decision making. Discrepant and strongly-held shared mental models may lead to misjudging environmental changes, especially in condition that emerging market numbers in an industry is high, and consensus to technology innovation in an industry still lack. Improper shared mental models can generate mistaken business models, which further bring about organizational decline. Keeping flexible in learning and improving existing mental models and consequent business models is crucial for entrepreneurial initiates to avoid failure.